IN-SERVICE TEACHERS’ PERCEPTION ABOUT THE EFFECTIVENESS OF THE USE OF MULTIMEDIA IN TRAINING OF SCIENCE - Singh, Vijay P. (SCHOOL SCIENCE, 2018)
Currently, the use of multimedia and ICT have revolutionised all aspects of the world of knowledge and information, including creation and development of content, storage, classroom transaction, assessment and evaluation, reporting, training of teachers, etc. This paper attempts to explore and report the views of science teachers about the effectiveness of multimedia content in teaching-learning of science at elementary level. These teachers participated in the Capacity Development Programme at RIE, Ajmer in the development and use of teaching-learning material through ICT integrated pedagogy at elementary level. The sample consisted of 11 in-service teachers from Uttarakhand, J&K and Rajasthan. The participants were exposed to a set of multimedia animated content in science in a session and their opinions were collected through an opinionnaire constructed for the purpose. The tool contained 16 items asking their opinion in affirmation or negation, four items about grading of the multimedia content and one item inviting their suggestions and comments in descriptive form. The analysis of the responses indicates that they found the use of multimedia very useful, sensitising, and interesting. However, most of the teachers indicated that the use of such multimedia cannot replace the teachers in classroom and that there is a need of teachers’ intervention after viewing the multimedia content. Some of the teachers indicated that the use of such multimedia is difficult in rural areas due to lack of proper infrastructural facilities.